Odpowiedź :
- Zadanie 1
A. [tex]\frac{11}{13} - \frac{5}{13} = \frac{6}{13}[/tex]
B. [tex]\frac{10}{13} - \frac{5}{13} = \frac{5}{13}[/tex]
C. [tex]\frac{12}{13} - \frac{4}{13} = \frac{8}{13}[/tex]
D. [tex]\frac{11}{13} - \frac{4}{13} = \frac{7}{13}[/tex]
Odpowiedź B.
- Zadanie 2
A. [tex]\frac{7}{9} - \frac{1}{9} = \frac{6}{9} = \frac{2}{3}[/tex]
B. [tex]\frac{9}{12} - \frac{1}{12} = \frac{8}{12} = \frac{2}{3}[/tex]
C. [tex]\frac{23}{24} - \frac{5}{24} = \frac{18}{24} = \frac{3}{4}[/tex]
D. [tex]\frac{31}{36} - \frac{7}{36} = \frac{24}{36} = \frac{2}{3}[/tex]
Odpowiedź C.
- Zadanie 3
[tex]9\frac{6}{11} - 6\frac{4}{11} = 3\frac{2}{11}[/tex]
A. [tex]10\frac{8}{11} - 8\frac{6}{11} = 2\frac{2}{11}[/tex]
B. [tex]7\frac{3}{11} - 4\frac{5}{11} = 2\frac{9}{11}[/tex]
C. [tex]8\frac{4}{11} - 5\frac{6}{11} = 2\frac{9}{11}[/tex]
D.[tex]5\frac{9}{11} - 2\frac{7}{11} = 3\frac{2}{11}[/tex]
Odpowiedź D
- Zadanie 10
a) [tex]\frac{3}{8} - \frac{1}{3 } = \frac{9}{24} - \frac{8}{24} = \frac{1}{24}[/tex]
b) [tex]\frac{5}{9} - \frac{1}{10} = \frac{50}{90} - \frac{9}{90} = \frac{41}{90}[/tex]
c) [tex]\frac{6}{7} - \frac{4}{5} = \frac{30}{35} - \frac{28}{35} = \frac{2}{35}[/tex]
d) [tex]\frac{8}{9} - \frac{4}{7} = \frac{56}{63} - \frac{36}{63} = \frac{20}{63}[/tex]